The Value of the Demonstration Method Based on Animated Videos to Improve Schilderen’s Speaking Skill at Ra Alaika - Dea Monica; Raoda Tul Jannah Maruddani; Annajmi Annajmi; Mardiana Mardiana; Kompri Kompri; Rafik Darmansyah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to improve the speaking ability of 5-6 year old children in Raudhatul Athfal Alaika, Kemingking Dalam Village, Taman Rajo District, Muaro Jambi Regency, by using a demonstration method based on animated videos. This method involves teachers showing certain steps directly in front of children, so that the learning process becomes more interactive and enjoyable. The main challenge faced in teaching is the lack of interesting methods, which results in children feeling bored and having difficulty understanding the subject matter. The research design uses the Classroom Action Research (CAR) approach with two cycles, each cycle includes the planning, implementation, observation, and reflection stages. Data were collected through careful observation of children's participation and responses during the learning process. The data were then analyzed using the average test and learning completeness to measure the improvement in children's speaking ability. The results of the pre-cycle showed that only 10 children were included in the BSH category in answering questions and constructing simple sentences, with a distribution of values ​​consisting of 4 children in the BB category, 5 children in the MB category, and 1 child in the BSB category in expressing ideas. After cycle I, all children showed improvement, entering the MB and BSH categories in each language skill indicator. In cycle II, all children achieved the BSB criteria, were able to answer more complex questions, express ideas better, and understand the concepts contained in the storybook. The conclusion of this study shows that the animated video-based demonstration method is very effective in improving children's speaking skills, expanding vocabulary, and providing an understanding of language use in a more real context. This method also creates a fun learning atmosphere, so that children are more motivated to actively participate in learning